Gilles Deleuze: alle radici di un divenire non dialettico - Remiddi, Sofia (B@belonline, 2022)
The essay aims to investigate the permanence of the theme of conflict within the philosophy of Gilles Deleuze, by making particular reference to its link with the concept of becoming. Furthermore, it will be shown how conflict is conceived within a non-dialectical and oppositional logic. Starting from Roberto Esposito’s criticisms about the absence of ‘negative’ in Deleuzian philosophy and from Andrew Culp’s need to restore the dark side of the french philosopher, we will go back to the root of the conflict by identifying it in the thought of Heraclitus to show how the Ephesian remain a constant reference in deleuzian philosophy. In this respect, fragment B 52 will be used as a guideline to retrace the interpretation of Nietzsche in Philosophy in the Tragic Age of the Greeks, and of Kostas Axelos in Héraclite et la philosophie. Thus, we will have the opportunity to recognize that struggle and contention are intrinsic to the deleuzian ontology by binding to the conflict thinker par excellence, even though they have no affinity with a frontal clash of affirmation and negation.